Living on the frontlines: Perspective from Poonch and Kotli region of AJK - Shaheen Akhtar (Journal of Political Studies, 2017)
Kashmir conflict deeply impacts the lives of the people living along the 740km Line of Control (LoC), dividing former state of Jammu and Kashmir. The people living in the in Kotli and Poonch districts are extremely vulnerable to volatile conditions of the LoC which adversely affect their physical security, livelihood, socio-cultural life, educational development, psychological health and wellbeing. This study evaluates the impact of Kashmir conflict and escalation of tension on the LoC in the 1990s, the impact of 2003 ceasefire and recent LoC tension on the lives of the people living in villages on the zero line in Kotli and Poonch districts. It argues that human dimension of the Kashmir conflict should be recognized, ceasefire on the LoC institutionalized and stalemated political dialogue resumed to revive political process on resolution of Kashmir dispute.